Healthy Lifestyle and Mental Health in Hadith Review: Implementing the Prophet Muhammad - Ade Faris Hargianto; Ali Abdur Rohman (Dialogia, 2022)
Health is the main aspect that humans must take care of. The health crisis during the COVID-19 pandemic taught about the importance of maintaining health. Moreover, in Islam, health is part of the faith. This paper examines the implementation of Prophet Muhammad SAW in maintaining health.  The purpose of this study is to explore the hadiths of the Prophet about healthy lifestyles and their impact on mental health.  Researcher uses the library research method with a ma'anil hadith study approach. In data processing, researchers use the takhrij al-hadith bil maudhu'i method. Researchers use this method to explore hadith based on themes and topics of discussion in various aspects about health themes contained in the hadith. The result of this paper is the first thematic hadith related to health has been widely spread in the community.  Secondly, during the time of Prophet SAW in maintaining the health of the Prophet was exemplified by maintaining physical fitness by riding. Third, positive thoughts predominantly affect health.